Simplification of Land and Building Tax Revenue (PBB) before and after the Transfer in Increasing Regional Original Income (PAD) - Fatima, Nurul Asda; Syahril, Muhammad Akbar Fhad (Amsir Management Journal, 2022)
Based on Law no. 28 of 2009 concerning Regional Taxes and Regional Retribution (PDRD), Fee for Land and Building Rights Acquisition (BPHTB) and the Rural and Urban Land and Building Tax (PBBP2) were transferred to local taxes. PBB-P2 was previously a tax which is managed by the central government and its receipts distributed to regions in a certain proportion. This research was conducted with the aim of knowing the differences in Land and Building Tax receipts in increasing Regional Original Income (PAD) before and after the enactment of Law no. 28 Year 2009.